Dose banding – Weighing up benefits, risks and therapeutic failure. Issue 7 (24th March 2022) - Duffull, Stephen
Abstract : Aims: Dose banding is a method of dose individualisation in which all patients with similar characteristics are allocated to the same dose. Dose banding results in some patients receiving less intensive treatment which risks a reduction in therapeutic benefit (iatrogenic therapeutic failure) because of variability not predicted by dose banding. This study aims to explore the effects of dose banding on therapeutic success and failure. Methods: This was a simulation study. Virtual patients were simulated under a simple pharmacokinetic model where the response of interest is the steady‐state average concentration. Clearance was correlated with a covariate used for dose banding. Dose individualisation was based on: one‐dose‐fits‐all, covariate‐based dosing, empirical dose banding, dose banding optimised for net therapeutic benefit and optimised for both benefit and minimising iatrogenic therapeutic failure. Results: The lowest and highest probability of target attainment (PTA) were 44% for one‐dose‐fits‐all and 72% for covariate‐based dosing. Neither dosing approach would result in iatrogenic therapeutic failure as lower dose intensities do not occur. Empirical dose banding performed better than one‐dose‐fits‐all with 59% PTA but not as good as either optimised method (64–69% PTA) while carrying a risk of iatrogenic therapeutic failure in 25% of patients. Optimising for benefit (only) improved PTA but carried a risk of iatrogenic therapeutic failure of up to 10%. Optimising for benefit and minimising iatrogenic therapeutic failure provided the best balance. Conclusion: Future application of dose banding needs to consider both the probability of benefit as well the risk of causing iatrogenic therapeutic failure.